KETERLIBATAN DAN PENGARUH POLITIK HUKUM TERHADAP IKLIM INVESTASI DI INDONESIA - Akmal Ricko Ferry Anantha; Dominikus Rato; Moh. Ali (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2022)
Legislation is an inseparable part of our country's identity as a state of law. In the process of forming legislation, it is closely related to legal politics which is one of the important elements in the running of a country. will be formed about what will be used as criteria to regulate something. So that it can be seen directly that the involvement and influence of legal politics is very large, a particular example is towards all rules made from the results of legal politics of legislative councils which affect all aspects of development in Indonesia including the investment climate in Indonesia. Investment is one of the drivers of the economy in Indonesia so that the arrangements must be made in a fundamental and detailed manner so that it can have a positive effect on the economy and investment in Indonesia. One of the legal products regarding investments made by the legislature is in Law Number 25 of 2007 namely concerning Investment, in enforcing this Law there are two categories of influence, namely positive and negative. If the positive influence created by the Investment Law applies to the general public then it will be good, but if it only applies to certain parties then it will be a negative influence.